Human Resource Empowerment through Community Service: Integrating Coastal Environmental Action and Jumputan Batik Training for Cultural Preservation at Pantai Baru - Eko Yulianto, M.B.A.; Innayah; Fijai, Ahmad; Larasati, Adelia Ayu; Khoi, Le Ngoc Minh (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2024)
Purpose • This community service program aimed to empower the human resources (HR) of the Pantai Baru coastal community through an integrated collaboration between beach clean-up activities and jumputan batik training involving Vietnamese students. The initiative sought to promote coastal environmental sustainability, preserve local cultural heritage, enhance ecological awareness, and strengthen community-based creative economic capacity. Methods - The program was implemented using a participatory and collaborative approach, emphasizing active involvement from coastal communities, beach management authorities, and university partners. Result and discussions - The activities were successfully conducted, as reflected in the high level of participant engagement and positive responses throughout the program. Beach clean-up actions significantly reduced plastic waste and improved collective awareness of environmental responsibility. Simultaneously, the jumputan batik training enhanced participants’ technical skills, creativity, and understanding of cultural preservation. The combination of environmental action and cultural education fostered stronger community participation and cross-cultural interaction. Conclusion - The integration of coastal environmental conservation and cultural skill development proved effective in strengthening human resource empowerment in coastal communities. This collaborative model demonstrates potential for replication as a sustainable community service framework that simultaneously addresses environmental challenges, cultural preservation, and local economic empowerment.